Theories of continental drift - VEERAIYAN, VISHVANTH D; VEERAIYAN, DEEPAK NALLASWAMY (The journal of contemporary issues in business and government, 2020)
Continental drift is the process of Continental plates moving. The movement is very slow, and it might take even years to show the impact on the Earth. The movement depends on gravity, convection drift, and plate formation. Gravity impacts the movements as the mantle(The layer below the crust) is always spinning because of gravity and the plates are located on the mantle. Convection drift impacts on the movement because convection drift is a cycle of melting and cooling of rocks in the mantle which can slowly impact the movement of the Plate. Plate Formation also affects the way the plates move as the new plates formed pushes the nearby plates causing Movement.